Length-Weight Relationships and Relative Condition Factor of the Mullet, Rhinomugil Corsula (Hamilton, 1822) In the Sitakunda Coast of the Bay of Bengal, Bangladesh (Bangladesh Journal of Zoology, 2021)
This study deals with the length-weight relationship and relative condition factor (Kn) of 2480 specimens of Rhinomugil corsula (Hamilton, 1822), ranging from 3.5 cm to 29.5 cm total length and 0.40 g to 235.34 g weight, sampled monthly for two years period from March 2016 to February 2018 from the Sitakunda Coast of the Bay of Bengal, Bangladesh. Arithmetic form of equations for length (TL) and weight (W) of fish showed curvilinear relationships in male: W=0.0081TL3.016, female: W= 0.0083TL3.058 and combined sex: W=0.0076TL3.052, while logarithmic scale showed linear relationships in male: LogW=-2.122+3.016LogTL, female: LogW=-2.09+3.058 TL and combined sex: LogW=-2.121+3.052TL. In all the cases the coefficient of correlations between length and weight were positive and highly significant (P